Perceived behavioral control and habit as key factors in reducing plate waste practices - Indarti Yuli; Khomsan Ali; Martianto Drajat; Ekayanti Ikeu (BIO Web of Conferences)
Background: Nutritional status is indirectly influenced by food security (1); therefore, ensuring food security is a fundamental factor in addressing nutritional problems in Indonesia. Plate waste practice represents a form of food waste behavior that negatively impacts food security. Understanding the determinant variables that influence this behavior is crucial for developing effective strategies to address and modify it. Objective: This study aimed to identify factors associated with the practice of plate waste. Methods: The study employed a cross-sectional design and utilized simple random sampling as the sampling method. Based on Cochran's formula, the sample size consisted of 140 high school students in Jember, Indonesia. Results: Knowledge (p = 0.035), perceived behavioral control (p = 0.001), habit (p = 0.001), hunger level (p = 0.001) and food preference (p = 0.010) were significantly associated with plate waste practices in the bivariate analysis. Based on the multivariate analysis, perceived behavioral control (p = 0.032), habit (p < 0.001*) and hunger level (p < 0.001*) were identified as predictor variables for plate waste practices. Designing interventions targeting these variables, particularly perceived behavioral control and habits, has the potential to effectively reduce plate waste practices.